Expert views on screening for tuberculosis infection in patients commencing treatment with a biologic agent - Sultana1,2, Adiba; Battista Migliori3, Giovanni; D’Ambrosio,4, Lia; García-García5, José-María; Rossato Silva6, Denise; Adrian Rendon5, Luis; R Codecasa7, Luigi; Blanc8, Francois-Xavier; Tiberi9, Simon; W M Ong10,11,12, Catherine; Heffernan13, Courtney; Sotgiu14, Giovanni; et al. (Jornal brasileiro de pneumologia, 2024)
Objective: Many biologic agents cause some degree of immunosuppression, which can increase the risk of reactivation of tuberculosis infection (TBI). This risk is variable between individual biologics. We aimed to assess current (and recommended) clinical practice of TBI screening and treatment among patients initiating treatment with biologic agents. Methods: An online questionnaire was distributed via email to members of the Global Tuberculosis Network and associated professional organisations to seek insights into the screening for and treatment of TBI in patients treated with biologics. Results: A total of 163 respondents in 27 countries answered at least one question. For all biologics described in the questionnaire, respondents advised increasing screening relative to current practice. Observed and supported TBI screening rates in patients treated with TNF-a inhibitors were high, especially for older TNF-a inhibitors. Most participants supported TBI screening in patients treated with B- or T-cell inhibitors but not in those treated with interleukin inhibitors. Guideline awareness was higher for TNF-a inhibitors than for other biologic classes (79% vs. 34%). Conclusions: Although respondents stated that TBI screening rates are lower than what they consider ideal, there was a tendency to recommend TBI screening in patients treated with biologics not known to be associated with an increased risk of TBI. As a result, there is a potential risk of over-screening and over-treatment of TBI, potentially causing harm, in patients treated with biologics other than TNF-a inhibitors. There is a need to research the risk of TBI associated with biologics and for guidelines to address the spectrum of TBI risk across all types of biologics.